2018
DOI: 10.1007/s10750-018-3796-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of habitat and survey criteria for the great crested newt (Triturus cristatus) in Scotland: a case study on a translocated population

Abstract: The great crested newt Triturus cristatus has declined across its range due to habitat loss, motivating research into biotic and abiotic species determinants. However, research has focused on populations in England and mainland Europe. We examined habitat and survey criteria for great crested newts in Scotland, with focus on a large, translocated population. Adult counts throughout the breeding season were obtained annually using torchlight surveys, and Habitat Suitability Index (HSI) assessed at created ponds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Blab and Blab (1981), besides shading and density of submerged vegetation, identified also pond area as the relevant characteristic for the abundance of crested newts. Other authors showed other key habitat features, including water chemistry and the structure of terrestrial habitat (Cooke, Cooke, & Sparks, 1994;Harper et al, 2018;Sztatecsny, Jehle, Schmidt, & Arntzen, 2004). Arntzen and Wallis (1999) nifex and its greater resistance to disturbed aquatic habitats (Meiling, Arntzen, van Delft, & Wielstra, 2015).…”
Section: Species-specific Habitat Preferencesmentioning
confidence: 97%
See 1 more Smart Citation
“…Blab and Blab (1981), besides shading and density of submerged vegetation, identified also pond area as the relevant characteristic for the abundance of crested newts. Other authors showed other key habitat features, including water chemistry and the structure of terrestrial habitat (Cooke, Cooke, & Sparks, 1994;Harper et al, 2018;Sztatecsny, Jehle, Schmidt, & Arntzen, 2004). Arntzen and Wallis (1999) nifex and its greater resistance to disturbed aquatic habitats (Meiling, Arntzen, van Delft, & Wielstra, 2015).…”
Section: Species-specific Habitat Preferencesmentioning
confidence: 97%
“…A hybrid zone is shown as a sharp cline. Habitat suitability for crested newts has been studied by several authors, but most of the research was focused just to one species (e.g., Blab & Blab, 1981;Harper, Downie, & McNeill, 2018;Oldham, Keeble, Swan, & Jeffcote, 2000;Unglaub, Steinfartz, Drechsler, & Schmidt, 2015). For instance, Maletzky et al (2007) evaluated habitat features of crested newt populations in northwestern Austria, where T. cristatus and T. carnifex come into contact and hybridize (Maletzky et al, 2008).…”
Section: Species-specific Habitat Preferencesmentioning
confidence: 99%
“…It is interesting that the most important suitability indices making the final HSI were not the local habitat characteristics such as presence of vegetation or the opportunities for foraging and shelter that were offered by a surrounding forest stand, but the index of predatory fish and invertebrate diversity, together with a pond area. However, it might be a result of our focus on local variables only, as results from some other previous studies indicate that the habitat quality (Ficetola & De Bernardi, ; Gustafson, Malmgren, & Mikusiński, ; Joly et al, ; Vuorio et al, ) and landscape connectivity (Harper et al, ; Langton et al, ) were regarded to be the one of the most important features shaping T. cristatus presence. Unlike in some previous studies that highlighted the correlation between aquatic plant diversity and the species presence (Gustafson, Pettersson, & Malmgren, ), we have not found any correlation between the two variables.…”
Section: Discussionmentioning
confidence: 93%
“…Presence of fish and shade of the water surface were found to have a negative influence on newts abundance (Denoël, Perez, Cornet, & Ficetola, 2013;Ficetola & De Bernardi, 2004;Gustafson, Andersen, Mikusi nski, & Malmgren, 2009). Among terrestrial habitat features, the most influential was connectivity between ponds (Harper, Downie, & McNeill, 2018;Langton, Beckett, & Foster, 2001) and general habitat quality (Ficetola & De Bernardi, 2004;Joly, Miaud, Lehmann, & Grolet, 2001;Vuorio, Heikkinen, & Tikkanen, 2013). However, it is important to assess the consistency of the habitat suitability index in different regions and identify factors affecting species occurrence at local, regional and continent scales.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, recent research (Harper, McNeill, & Downie, ) indicates that at least some of the new ponds are successful and hold substantial crested newt populations. Monitoring the habitats and abiotic conditions at the site in 2015 (Harper, Downie, & McNeill, ) indicated that the standard survey methods used in England are not fully appropriate for Scottish populations: in particular, the newts became active at lower temperatures at Gartcosh than in England, an observation also made by Paterson (). These findings emphasized the need to pay attention to local adaptations in widely distributed species.…”
Section: Protection Enhancement and Mitigationmentioning
confidence: 97%